(y+9)2*2-(y+5)2*2=28

Simple and best practice solution for (y+9)2*2-(y+5)2*2=28 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (y+9)2*2-(y+5)2*2=28 equation:


Simplifying
(y + 9) * 2 * 2 + -1(y + 5) * 2 * 2 = 28

Reorder the terms:
(9 + y) * 2 * 2 + -1(y + 5) * 2 * 2 = 28

Reorder the terms for easier multiplication:
2 * 2(9 + y) + -1(y + 5) * 2 * 2 = 28

Multiply 2 * 2
4(9 + y) + -1(y + 5) * 2 * 2 = 28
(9 * 4 + y * 4) + -1(y + 5) * 2 * 2 = 28
(36 + 4y) + -1(y + 5) * 2 * 2 = 28

Reorder the terms:
36 + 4y + -1(5 + y) * 2 * 2 = 28

Reorder the terms for easier multiplication:
36 + 4y + -1 * 2 * 2(5 + y) = 28

Multiply -1 * 2
36 + 4y + -2 * 2(5 + y) = 28

Multiply -2 * 2
36 + 4y + -4(5 + y) = 28
36 + 4y + (5 * -4 + y * -4) = 28
36 + 4y + (-20 + -4y) = 28

Reorder the terms:
36 + -20 + 4y + -4y = 28

Combine like terms: 36 + -20 = 16
16 + 4y + -4y = 28

Combine like terms: 4y + -4y = 0
16 + 0 = 28
16 = 28

Solving
16 = 28

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -7u-46=31 | | h(t)=-16t^2+36t+5 | | Y-8=2/3x | | 6d+57=39 | | 2x+3=2x-(3x+2x)+6 | | -6(-4x+3)-5x=7(x-2)-1 | | -5a+(-18)=22 | | -2(3+x)+3(2+2x)=1+4x | | 10x-3y-5x+13y= | | 10xsquare-3x-1=0 | | 2p-(-86)=52 | | 3600=200x-x^2 | | -4l+(-25)=55 | | 3x-13y=2forwhy | | 4(x-2)+2x=3(x-1)-11 | | -3e-72=-18 | | -214+-8(2x-3)=-334 | | 3v-36=-42 | | 10x+5=12y+5 | | 15y+20= | | 4r+(-12)=48 | | 15y/4=90 | | 2x-6+4x+28=6x+22 | | 3(x+1)x+4(x+3)=22 | | 4(2x-y)=2y+5 | | 147.1875=3r(3.14r^2) | | 0.4(x+25)-3=0.2(7x+10) | | 13x-4x=-63 | | 3y+4z=9fory | | 8x=6y+5 | | 22-6y+y^2-14=0 | | 83=15+2(x) |

Equations solver categories